(untitled) (Research, Society and Development, 2022)
In the Food and Nutrition Unit, there is the production and distribution of meals for communities and the University Restaurants are models for implementing the food policy within the scope of Brazilian public universities. In this study, we aimed to evaluate the hygienic-sanitary conditions of the areas/sectors of a University Restaurant. Data were collected from August to September 2018 with the application of two checklists, one weekly and the other monthly, which considered environmental hygiene conditions, cafeteria service, physical structure and hygiene. From the application of the monthly checklist, the reception area of foodstuffs was considered regular (66.9%), as well as the antechamber (63.5%), the pre-preparation of salads (69.0%) and the area for cleaning kitchen utensils (57.4%), whereas the cold room for fruit and vegetables was the only area that was unsatisfactory (47.8%). In the evaluation of the areas with the weekly check list, the areas with regular classification were the reception of foodstuffs (64.3%), the butcher shop (68.2%), pre-preparation of salads (59.3%), cooking (54.3%) and cleaning of kitchen utensils (57.4%), whereas the grain collection and juice preparation area was the only one classified as unsatisfactory (44.2%). Thus, it was possible to verify that the university restaurant has not been working under favorable conditions of hygiene and that the inadequate hygienic-sanitary conditions observed in some areas/sectors were linked to structural problems and production management, that is, inadequacy of control of the production process, that occurred from receiving the raw material to obtaining the final product – the meal.